KEBIJAKAN PENGAWASAN PEMERINTAH TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN NEGARA DALAM PENANGANAN PANDEMI COVID-19 - Erika Ayu Oktaviani; Sapto Hermawan; Waluyo (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This study aims to find out how the government's control policy is on accountability of state financial management in handling the Covid-19 pandemic. This writing uses a normative or doctrinal legal method, using a statutory and conceptual approach that is perspective. The data collection technique was carried out by literature study techniques and the data analysis technique used was the deductive method. Based on the results of the study, it was found that the impact of the Covid-19 pandemic on the economic sector triggered a spike in the poverty rate. The government provides a number of aids to increase people's purchasing power. The allocation of funds for handling Covid-19 is a sector prone to corruption. Therefore, it is necessary to have an internal control policy of the Government in preventing corrupt practices by irresponsible parties for the realization of a professional, reliable and competent state administration. One of the policies issued is the Instruction of the Minister of Home Affairs Number 1 of 2020 at the sixth diktu. In the instruction, the Government Internal Supervisory Apparatus (APIP) is mandated to carry out guidance and supervision of the implementation of Domestic Instructions by identifying risk points in the process of handling the Covid-19 pandemic disaster and ensuring the effectiveness of existing controls, carrying out monitoring activities related to compliance and effectiveness, improve governance, risk, control, and use of technology to support the implementation of effective internal control.